Colour contrast enhancement based on bright and dark stretching for Plasmodium Falciparum in malaria slide image - N. S. M. M., Hanif; Mohd Yusoff, Mashor, Prof. Dr.; Zeehaida, Mohamed, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.